Fishery Product Business Management Strategy In Teluk Kabung Utara Village, West Sumatra Province - Rizki Syakbana; Dewita Dewita; Sukendi Sukendi (Berkala Perikanan Terubuk, 2021)
This study aims to develop a fishery product business management strategy in TelukKabung Utara Village, Padang City. The research was conducted from 21 December2020 to 20 January 2021. The study was conducted using a qualitative approach tosurvey methods and direct observation in the field. Data collection was carried outthrough observation and in-depth interviews with a structured questionnaire instrument.Secondary data were obtained from related agencies in this study. The analysis used inthis research is descriptive analysis method and SWOT analysis to determine theappropriate management strategy. The results of the SWOT analysis show that thepriority strategy related to the management of fish processing units is to supportaggressive strategies, namely strategies that are carried out by utilizing all strengths toseize and take advantage of the greatest opportunities. The strategies for managingfishery product businesses in Teluk Kabung Utara Village are: 1) Maximizing the use ofa wide range of markets in high demand for products by conducting good coordinationamong fishery product business owners, 2) Maximizing the use of capital assistanceprovided by the government by Right in order to develop a fishery product business.